2018
DOI: 10.1111/crj.12960
|View full text |Cite
|
Sign up to set email alerts
|

First assessment of interferon gamma release assay results among healthcare workers at a general hospital in China

Abstract: Introduction China has a very high tuberculosis (TB) burden. The interferon‐gamma release assay (IGRA) is more specific for the diagnosis of latent tuberculosis infection (LTBI) than the tuberculin skin test, especially among populations with a high degree of coverage by the BCG vaccine. Objectives To evaluate the first screening of healthcare workers (HCW) for LTBI using the IGRA at a general hospital in Beijing. Methods A pilot screening program for LTBI was triggered by accidental contact between HCW and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…LTBI prevalence among household contacts was found to be relatively high (32-48%) (Zhang et al, 2019;Hu et al, 2012). The TB infection rate in healthcare workers (HCWs) was found to range from 15% to 70% depending on the level and the location of the hospital (Guo et al, 2018;Di et al, 2014). IGRA positivity was observed to be lower than 10% in schoolchildren and adolescents (Hu et al, 2013;Li et al, 2017).…”
Section: Ltbi Burden In Chinamentioning
confidence: 99%
“…LTBI prevalence among household contacts was found to be relatively high (32-48%) (Zhang et al, 2019;Hu et al, 2012). The TB infection rate in healthcare workers (HCWs) was found to range from 15% to 70% depending on the level and the location of the hospital (Guo et al, 2018;Di et al, 2014). IGRA positivity was observed to be lower than 10% in schoolchildren and adolescents (Hu et al, 2013;Li et al, 2017).…”
Section: Ltbi Burden In Chinamentioning
confidence: 99%
“…LTBI prevalence among household contacts varied from 32 to 48% [6,7]. The TB infection rate in healthcare workers was found to range from 15% to 70% [8,9]. IGRA positivity was observed to be lower than 10% in schoolchildren and adolescents [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found lower but substantial levels of LTBI among HCWs in China, ranging from 22% to 34%. [8][9][10] In a cross-sectional study of 31 health facilities in China, regular facility-based IPC training and implementation was associated with low HCW LTBI prevalence, 10 highlighting the importance of facility IPC policies.…”
mentioning
confidence: 99%